2018
DOI: 10.3390/ijerph15122745
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Physical Activity and Quality of Life in Pregnant Women in the Second and Third Trimester

Abstract: Background: The problem of an inadequate level of physical activity (PA) is important in the context of its relationship with the quality of life (QoL) of pregnant women. The aim of this study was to analyze the relationships between PA and QoL among pregnant women. Methods: The study analyzed 346 questionnaires filled in by pregnant women (157 in the second trimester and 189 in the third). The tool used for assessment of PA was the Pregnancy Physical Activity Questionnaire-Polish version (PPAQ-PL). The qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 55 publications
6
41
2
1
Order By: Relevance
“…The high scores in the physical domain were also consistent with the report by Tavoli et al [26]. Interestingly, in the QoL self-assessment by physically active women during uncomplicated pregnancy, the scores in the physical domain were next to lowest, while the highest scores were reported in the psychological domain [27]. In the present study, women who had lost a pregnancy reported lower QoL in the psychological domain.…”
Section: Discussionsupporting
confidence: 92%
“…The high scores in the physical domain were also consistent with the report by Tavoli et al [26]. Interestingly, in the QoL self-assessment by physically active women during uncomplicated pregnancy, the scores in the physical domain were next to lowest, while the highest scores were reported in the psychological domain [27]. In the present study, women who had lost a pregnancy reported lower QoL in the psychological domain.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have reported positive effects of PA on psychosocial status, such as quality of life (QoL), outside of confinement (Anokye et al, 2012;Vagetti et al, 2014;Krzepota et al, 2018;Ho et al, 2019). However, no study has so far investigated the relationship between PA and QoL during a period of confinement, such as the quarantine caused by COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…women in their third trimester reported mostly a tendency towards sedentary lifestyle, dominated by occupational type of PA, whereas those in their second trimester had a light level of PA and were oriented more towards household activities. Indeed, the second trimester of pregnancy is considered to be the most comfortable period during gestation, where women often feel more energetic and eager to be physically active [7]. Although, PA may decline before delivery due to excess body weight, lower back pain and pressure caused by the expansion of the uterus [32], our study demonstrated an elevated intensity of PA during the last trimester among ladies for occupational oriented activities.…”
Section: Plos Onementioning
confidence: 54%
“…A review published by Forczek et al in 2017 observed a net decline in activities in the first trimester of pregnancy, followed by a rise, after the 14 th week of gestation, with women mostly oriented towards occupational activities, housework/caregiving, active lifestyle combining essentially aerobic sports, such as walking and stationary cycling [30]. On the other hand, in a sample of Polish pregnant women, no differences were observed in terms of total PA, across the trimesters of pregnancy [7]. In our sample, the intensity and the type of PA increased in women of second and third trimester, compared to those in their first trimester.…”
Section: Plos Onementioning
confidence: 92%
See 1 more Smart Citation